1. Formal and Non-Formal Education Through Theatre54 - Kušnírová Eva (Sciendo, 2023)
The Frankfurt Declaration is a UNESCO document that reminds and re-emphasizes the importance of promoting and applying arts education to the curriculum of all member states. In 2019, the World Alliance for Arts Education (WAAE) organized an international conference called Arts Education for everybody? Every student? Everywhere? It opened a discussion on various topics about arts education (e.g., in society, in school reforms, opportunities for the education of pedagogues, interconnection with other fields, its application at different levels of schools, its future, possibilities to spread and communicate it in different countries of the world). The education through theatre also belongs to the field of arts education. The study reflects and maps the topic of formal and non-formal education through theater. It ponders the question What is the status of formal and non-formal education through theater nowadays? It points to interesting and inspiring projects, to institutions dedicated to the education through theatre, to the educational activities of professional cultural institutions, the position of drama education in the school system and beyond it, the education through theater at universities, as part of festivals, etc. It also brings an excursion into the education through theater in abroad, in the Czech Republic and Slovakia.